Effects of oocyte source on the developmental competence of in vitro matured goat oocytes fertilized by the intracytoplasmic sperm injection technique - Abdullah, Ramli; Wan-Khadijah, W.E.; Rahman, A. (2009)
This study evaluated the effects of oocyte source on in vitro maturation (IVM) and embryo developmental competence in goats by the intracytoplasmic sperm injection (ICSI) technique. Oocytes were obtained either by laparoscopic ovum pick-up (LOPU) or by slicing of abattoir ovaries. The donor does used for LOPU were superstimulated and their estrus was synchronized. Recovered oocytes from both sources were cultured in microdrops of IVM medium in the presence of CO(2) (5%) at 38.5 degrees C in a CO(2) incubator for 27 h. The ICSI was performed with immobilized sperm on the lid of a culture dish (35 mm) under an Olympus inverted microscope fitted with Narishige micromanipulators. Injected oocytes were cultured for < 192 h in mSOF medium in the CO(2) incubator. Although oocyte recovery per doe was higher (P < 0.05) in abattoir (27.3 +/- 3.0) than LOPU (17.6 +/- 2.5) source, better quality oocytes were obtained from LOPU. Oocyte maturation rate was higher (P < 0.01) in LOPU (73.8 +/- 3.0%) than abattoir-derived (54.0 +/- 0.7%) oocytes. Fertilization and cleavage rates (60.9 +/- 2.1% and 83.1 +/- 2.6%, respectively) were also higher (P < 0.05) with LOPU than abattoir-derived (50.6 +/- 2.3% and 69.3 +/- 4.5%) oocytes. A higher (P < 0.05) proportion of LOPU-derived embryos (20.0 +/- 1.2%) progressed to the morula stage than abattoir (11.3 +/- 4.7%) source. In conclusion, better maturation, fertilization, and embryo development rates were obtained with LOPU-derived oocytes than with the abattoir source.